Stability of Platinum in Sulfuric Acid Solution Studied by Electrochemical Quartz Crystal Microbalance - Yadav, Amar Prasad (Journal of Nepal Chemical Society, 2013)
The stability of electrodeposited platinum electrode in 0.5 M H2SO4 solution has been studied under potentiodynamic and potentiostatic conditions using electrochemical quartz crystal microbalance (EQCM). In potentiodynamic polarization, cyclic voltammetry (CV) was carried out from 0.0 to 1.4 V at the scan rate of 0.01 V s-1 while in potentiostatic polarization, potential was stepped from 0.45 V to higher anodic potential limits of 0.75V, 1.0V, 1.1V, 1.2V, 1.4V, and 1.5V and corresponding mass change resulting from the formation of PtO was measured by EQCM. The results of CV and EQCM revealed that the Pt surface was covered with PtO in 0.65 < E< 1.5 V. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9233 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 24-27 Uploaded date : 12/3/2013